Psychosocial work environment and leisure-time physical activity: the Stormont Study. (1st March 2015) - Houdmont, J.; Clemes, S.; Munir, F.; Wilson, K.; Kerr, R.; Addley, K.
Abstract: Background: Research findings on the relationship between the psychosocial work environment and leisure-time physical activity (LTPA) are equivocal. This might partly be due to studies having focused on a restricted set of psychosocial dimensions, thereby failing to capture all relevant domains. Aims: To examine cross-sectional associations between seven psychosocial work environment domains and LTPA in a large sample of UK civil servants and to profile LTPA and consider this in relation to UK government recommendations on physical activity. Methods: In 2012 Northern Ireland Civil Service employees completed a questionnaire including measures of psychosocial working conditions (Management Standards Indicator Tool) and LTPA. We applied bivariate correlations and linear regression analyses to examine relations between psychosocial working conditions and LTPA. Results: Of 26000 civil servants contacted, 5235 (20%) completed the questionnaire. 24% of men and 17% of women reported having undertaken 30min or more of physical activity on five or more days in the past week. In men, job control (−0.08) and peer support (−0.05) were weakly but significantly negatively correlated with LTPA, indicating that higher levels of exposure to these psychosocial hazards was associated with lower levels of LTPA. Job role (−0.05) was weakly but significantly negatively correlated with LTPA in women. These psychosocial work characteristics accounted for 1% or less of the variance in LTPA. Conclusions: Longitudinal research to examine cause–effect relations between psychosocial work characteristics and LTPA might identify opportunities for psychosocial job redesign to increase employees' physical activity during leisure time.